An Empirical Analysis of Analysts' Capital Expenditure Forecasts: Evidence from Corporate Investment Efficiency* - Choi, Jin Kyung; Hann, Rebecca N.; Subasi, Musa; Zheng, Yue (Contemporary Accounting Research, 2020)
ABSTRACT We examine whether the information conveyed in a relatively new analyst research output—capital expenditure (capex) forecasts—affects corporate investment efficiency. We find that firms with analyst capex forecasts exhibit higher investment efficiency. This effect is stronger when the forecasts are issued by analysts with higher ability or greater industry knowledge. Moreover, the effect of capex forecasts on investment efficiency varies with the signals they convey about future growth opportunities—positive‐growth signals are more effective in reducing underinvestment, while negative‐growth signals are more effective in reducing overinvestment. Cross‐sectional tests suggest that these effects operate at least in part through both a financing channel and a monitoring channel. Taken together, our results suggest that analysts' capex forecasts convey useful information about firms' growth opportunities to managers and investors, which can facilitate efficient investment.